ERN1 modifies the effect of glutamine deprivation on tumor growth related factors expression in U87 glioma cells - O. H. Minchenko; A. P. Kharkova; O. S. Hnatiuk; O. Y. Luzina; I. V. Kryvdiuk; A. Y. Kuznetsova (The Ukrainian Biochemical Journal, 2018)
The expression of a subset of genes encoding important tumor growth related factors in U87 glioma cells with ERN1 (endoplasmic reticulum to nucleus signaling 1) loss of function as well as upon glutamine deprivation was studied. It was shown that glutamine deprivation down-regulated the expression level of ATF6 (activating transcription factor 6), EIF2AK3/PERK (eukaryotic translation initiation factor 2 alpha kinase 3), GLO1 (glyoxalase I), BIRC5 (baculoviral IAP repeat-containing 5), and RAB5C (RAB5C, a member of RAS oncogene family) mRNAs in control glioma cells. At the same time, the expression level of HSPB8 (heat shock 22kDa protein 8) and HSPA5/GRP78 (heat shock protein family A (Hsp70) member 5) mRNAs was resistant to glutamine withdrawal in these glioma cells. It was also shown that inhibition of ERN1, which controled cell proliferation and tumor growth, modified the effect of glutamine deprivation on the expression levels of most studied genes in U87 glioma cells: up-regulated the expression of ATF6 and HSPA5 genes and enhanced sensitivity of EIF2AK3 and BIRC5 genes to glutamine withdrawal. Furthermore, the expression of all studied genes, except EIF2AK3, was down-regulated in ERN1 knockdown glioma cells in the presence of glutamine. It was demonstrated that glutamine deprivation affected the expression of most studied genes in ERN1 dependent manner and that these changes possibly contributed to the suppression of glioma growth from cells without ERN1 signaling enzyme function.